STRATEGIC COMMUNICATION ROLE OF AHA CENTRE CRISIS MANAGEMENT (ASEAN COORDINATING CENTRE FOR HUMANITARIAN ASSISTANCE ON DISASTER MANAGEMENT) IN RESPONDING TO THE 2018 CENTRAL SULAWESI HAMMER EARTHQUAKE - Zahra Zeitira; Muhammad Faisal; Claudy Putri Diguna; La Mani (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
Natural disasters are problems that need to be overcome together. In this regard, the presence of the AHA Centre is a solution to facilitate cooperation, coordination, and collaboration between member countries in overcoming disasters that occur. The purpose of this paper is to provide research results related to the description and disaster risk communication strategies of the AHA Centre in ASEAN countries, especially in response to the earthquake in Palu, Central Sulawesi in 2018. The method used in this research process is a constructivist paradigm with a qualitative research approach. The results of the study showed that the AHA Centre achieved success in its role to coordinate disaster management strategies for the earthquake in Palu, in 2018 by taking action to facilitate cooperation both internally and externally through creative active collaboration with outside parties other than ASEAN. As well as its crisis management strategic communication so far is quite good but still strives to achieve maximum improvement so that it can always survive and help member countries in ASEAN.